An evaluation of Bangladesh automated clearing house system on Bank Asia Ltd. (Scotia branch) - Tabassum, Farzana (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.